CALL Project-Based Program to Enhance Student-Teachers’ TEFL Skills - Milad, Marine (Journal of language teaching and research, 2022)
Students-teachers are students who study to become Teaching English as a Foreign language (TEFL) teachers. They receive teaching trainings, observe certified teachers’ teachings performance, and do some supervised teaching practices in EFL classrooms for the elementary and secondary stages.  The current study aims at presenting a supplementary program to support a practical course on methods of teaching English as a foreign language for the elementary stage. The supplementary program has been developed by the researcher to enhance Arab Open University (AOU) student-teachers’ skills of teaching listening, speaking, reading, writing, and vocabulary for elementary stage pupils through a language project that focuses on instilling social values in these young pupils. This was mainly done with samples of practical examples, interactive discussions and tasks of practical nature posted on Learning Management System (LMS) following Computer-Assisted Language Learning (CALL) methodology in accordance with the Intended Learning Outcomes (ILOs) of the course. The study has adopted the Constructoactive Model developed by Sahakian and Ghoneim (2007) to promote pupils’ knowledge of different methods of teaching English as a foreign language and to familiarize young pupils with good social values and their related vocabulary items. In addition, the supplementary program has adopted Stoller's (1997) model for developing project work. The model has proved to be helpful in promoting the student-teachers’ performance in teaching different language skills, writing lesson plans and giving demo class presentations for the developed lesson plans by using PowerPoint/Prezi presentations, open-source video/audio links and a number of software programs (such as Kahoot, Quizlet, and Grammarly).